The Roles of Beclin 1 Expression in Gastric Cancer: A Marker for Carcinogenesis, Aggressive Behaviors and Favorable Prognosis, and a Target of Gene Therapy - Zheng, Hua-chuan; Zhao, Shuang; Xue, Hang; Zhao, En-hong; Jiang, Hua-mao; Hao, Chang-lai (Frontiers in Oncology, 2020)
Beclin 1 is an autophagy-related protein that is encoded by Becn1, and plays a role in tumorigenesis, neurodegeneration and apoptosis. Here, the aggressive phenotypes and relevant proteins were screened after Beclin 1 expression was altered in gastric cancer cells. We also observed the effects of Beclin 1 on gastric carcinogenesis using Becn1 knockout mice. Finally, clinicopathological significances of Beclin 1 were analyzed using meta- and bioinformatics analyses. Becn1 overexpression was found to inhibit proliferation, glucose metabolism, migration and invasion of gastric cancer cells, whereas its knockdown caused the opposite effects. Beclin 1 suppressed the tumor growth by decreasing proliferation and increasing apoptosis. Becn1 deletion in gastric pit, parietal and chief cells could not cause any epithelial lesion. Beclin 1-mediated chemoresistance was closely linked to the autophagy, Bax underexperssion, and the overexpression of Bcl-2, LRP1, MDR1, and ING5. Bioinformatics analysis showed higher Becn1 mRNA expressionin intestinal- than diffuse-type carcinomas (P<0.05), and in male than female gastric cancer patients (P<0.05). Becn1 hyperexpression was positively associated with both overall and progression-free survival rates of the cancer patients (P<0.05). Meta-analysis showed that down-regulated Beclin 1 expression in gastric cancer was positively with lymph node metastasis, TNM staging, dedifferentiation and poor prognosis of gastric cancer (P<0.05). Becn1-related signal pathways in gastric cancer included prostate, lung, renal, colorectal, endometrial and thyroid cancers, glioma, and leukemia, the metabolism of amino acid, lipid and sugar, and some signal pathways of insulin, MAPK, TRL, VEGF, JAK-STAT, chemokine, p53, lysosome, peroxidome and ubiquitin-mediated protein degradation (P<0.05). These suggested that Beclin 1 might be considered as a potential marker of gastric carcinogenesis, aggressiveness and prognostic prediction, and as a target of gene therapy.